The history of non-fungible crypto tokens (NFTs) art In the Kingdom of Saudi Arabia (Al-Academy, 2023)
This research is concerned with documenting and chronicling the art of NFTs art in the Saudi artistic cultural scene, the importance of which stems from the lack of scientific sources that document this field until the preparation of this research and aims to trace historically the emergence of the field of NFTs art in the Kingdom of Saudi Arabia in the arts sector through the experiences of Saudi artists. The most prominent events for the culture, arts and technology sector, and other Saudi sectors. The research dealt with the history of the emergence of the field of NFTs art, which extends from the history of digital arts, and reviewed the most famous works of NFTs art.As a result of the technical revolution and the artistic movement that the world is witnessing in the direction of investing in digital arts, this movement has moved to the Saudi artistic cultural scene through the experiences of Saudi artists and emerged from the artist Rashid Al-Shasha’i, and after him the era of Al-Amoudi. As for the major Saudi sectors, the role of the Ministry of Communications and Information Technology and the Ministry of Culture, represented by the Visual Arts Authority, emerged for organizing conferences that paved the way for the emergence of this field in the Kingdom, followed by initiatives for the activities of some sectors to benefit from the technical capabilities of the field of NFTs art.